Características hematológicas de teleósteos brasileiros: II. Parâmetros sangüíneos do Piaractus mesopotamicus Holmberg (Osteichthyes, Characidae) em policultivo intensivo - Tavares-dias, Marcos [UNESP]; Tenani, Rosilene A; Gioli, Leonardo D; Faustino, Christiane D (Sociedade Brasileira de Zoologia, 1999)
Hematological parameters of freshwater fish Piaractus mesopotamicus (Holmberg, 1887) kept in an intensive polyculture system were determined. The correlations among these parameters as well as those between the parameters and the biometric data (total weight and standard length) were also analyzed. Erythrocytes count was 1.708±0.42 x 10(6)/µl, hemoglobin 6.6±2.0 g% of blood and hematocrit 32.5±4.6%, mean corpuscular volume (MCV) 209.8±69.5%, mean corpuscular hemoglobin (MCH) 40.2±5.6 pg and mean corpuscular hemoglobin concentration (MCHC) 21.4±8.4%. The percentage of defense blood cells including leucocytes and thrombocytes, was studied. The percentage of thrombocytes was 61.4±10.0%, lymphocytes 21.7±1.8%,neutrophils 10.4±11.0%, monocytes 4.7±3.3% and special granulocitic cells 1.8±2.0%. The number of erythrocytes was positively correlated with the hemoglobin rate and negatively correlated with MVC. Hemoglobin was positively correlated with MCHC whereas hematocrit was negatively correlated with MCHC and MVC. Contrarily, leukocytes did not show correlations among themselves or with the hematological parameters and biometric data.
Hematological characteristics of Brazilian teleosts: II. Blood parameters of Piaractus mesopotamicus Holmberg (Osteichthyes, Characidae) in an intensive polyculture system
Keywords: Piaractus mesopotamicus; blood; erythrocytes; freshwater fish; leucocytes; thrombocytes